A systematic review of cheerleading injuries: epidemiological characteristics, biomechanical mechanisms, and prevention strategies - Deng, Chenliang; Yu, Qiaoyan (Frontiers in Public Health, 2025)
ObjectiveAgainst the backdrop of global cheerleading popularity, this study systematically analyzes injury characteristics, biomechanical mechanisms, and prevention strategies to provide evidence for safety risk control in cheerleading.MethodsJournal articles published between January 1, 1991, and April 18, 2025, were retrieved topics from the SCI/SSCI subdatabase of web of science core collection using the keywords “cheerleading,” “cheerleader,” and “injuries.” Following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) screening procedures, 27 studies were ultimately included for analysis.ResultsEpidemiological data show that from 2010 to 2019, the United States cheerleading injuries exhibited an annual 15% decline in overall rates, but concussions increased by 44% annually, and hospitalization rates rose by 9%. Pediatric injuries primarily affected 12–17-year-old females, with 5–11-year-olds showing a significantly higher proportion of moderate-to-severe injuries (46.5%) compared to 12–19-year-olds (28.2%). Stunt-related injuries accounted for the highest proportion (53.2%), with high-risk collaborative maneuvers (such as basket tosses and pyramids) being primary causes of catastrophic injuries. After the international cheer union (ICU) banned hard-surface basket tosses in 2006–2007, the catastrophic injury rate dropped from 1.55 to 0.40 cases per million participants. Biomechanical studies indicate flip movements carry a 67.92% injury rate, while jumping/dance combinations have a 48.15% rate. Ankles (44.9%) and wrists/hands (19.3%) are most vulnerable due to joint overload and imbalance during tosses, stunts, and braces, with lumbar injuries directly linked to excessive training intensity and poor technique. Prevention strategies should integrate closed-chain eccentric training with Kohonen neural network-based action safety assessment, alongside strengthened rule restrictions (e.g., mandatory use of specialized mats, prohibited hard-surface practice) and personnel qualification management.ConclusionCheerleading injury prevention requires a multidimensional strategy: Implement biomechanical interventions (closed-chain eccentric training and movement technique optimization) to enhance muscle endurance and action control precision; Promote rule optimization and coach certification, establishing standardized difficulty criteria for each level and a risk factor–based assessment and prevention system; Develop pediatric protection standards and professional training systems, and pay attention to monitoring and recovering from excessive fatigue.